Sharia Yes, Sharia State No: Negosiasi dan Akomodasi Syari’ah di Indonesia - Mutaqin, Zezen Zaenal (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
Syafiq Hasyim. 2023. Shariatization of Indonesia, the Politics of the Council of Indonesian Ulama (Majelis Ulama Indonesia, MUI). Leiden: Brill. Wael Hallaq. 2013. The Impossible State, Islam, Politics, and Modernity's Moral Predicament. New York: Columbia University Press. The two works discussed in this book review examine how Sharia norms are negotiated and accommodated in modern nation-states. This process is inevitable as Muslims are confronted with the persistence of the nation-state and the theological obligation to apply Sharia norms in their lives. Although Hallaq's work is very pessimistic in saying that paradigmatically the two systems are impossible to reconcile, his work can serve as an important background for understanding Hasyim's work which discusses in detail how Sharia is accommodated in the legal order and public life in Indonesia, highlighting the role of the MUI as the main institution of this accommodation process. Hasyim's work tries to answer three important questions: how and in what way MUI plays a role in the process of sharization; what its implications in law and public life in Indonesia are and how the process came about; and how the state and society respond to this sharization.